INTEGRATED EXCELLENT MATERNITY NURSING CARE FOR LOW -BIRTH-WEIGHT INFANT AT SANTI MEILALA INPATIENT PRIMARY CLINIC MEDAN POLONIA DISTRICT, NORTH SUMATRA PROVINCE IN 2025 - Sihaloho, Pelida; Marliani; Furi Estie Honez; Sawir Amra; Elseria Situmorang; Dinna Olifia Nainggolan; Fasya Amanda, (Mitra Husada Health Internasional Conference (MIHHICo), 2025)
According to the World Health Organization (WHO, 2021), low birth weight (LBW) refers to infants who weigh less than 2,500 grams at birth. Meanwhile, Juriyah et al. (2024) state that LBW occurs from birth up to the first 24 hours after delivery. Infants with low birth weight are more susceptible to infectious diseases and frequently experience complications that may lead to death, as their organs are not yet fully developed. In Indonesia, several factors increase the risk of LBW, including maternal age under 20 or over 35 years, short intervals between pregnancies, a history of delivering LBW infants, strenuous physical labor, working without adequate rest, extreme poverty, underweight and poor nutritional status, smoking habits, alcohol consumption, anemia, preeclampsia or hypertension, infections during pregnancy, multiple pregnancies, congenital abnormalities in the baby, and infections related to pregnancy.